A Survey On The Intention Of The Nurses' Of Different Generations To Leave Their Job And Profession And Their Organizational And Professional Commitment - Semra Mert Haydari; Gülseren Kocaman; Merlinda Aluş Tokat (Association of Nurse Managers, 2017)
INTRODUCTION: For preventing nurses leaving the job and profession, there is a need to determine their attitudes towards job and profession. To analyze the intention of the nurses' to leave their job and profession as well as their commitment to the organization and the profession across generations. METHODS: The 790 nurses from a university and two public hospitals who represented X and Y generations participated. The data was collected with the Socio-Demographic form, Organizational and Professional Commitment Scales. For data analysis chi-square and t test were used. RESULTS: The 57.6% of nurses had a high intention to leave their jobs and 55.9% to leave their profession. Compared to the X Generation, the intention of the Y Generation nurses to leave their job and profession was found significantly higher. The results reveal that nurses perceive organizational and professional commitment at a low to moderate level. Compared to Y, the X Generation received for the affective, normative and continuance aspects of organizational commitment and continuance professional commitment were found significantly higher. DISCUSSION AND CONCLUSION: The characteristics of different generations should be taken into consideration while determining the strategies for the nurses to remain in their jobs and professions and promoting their commitment.